Antibiotic Sensitivity Of Acute Respiratory Infection Patients In Bhayangkara Hospital Bengkulu. - Zamharira Muslim; Putri Widelia Welkriana; Regita Pratiwi Mahardika (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
The high incidence of antibiotic resistance in the treatment of infections today is very worrying. The main therapy in patients with acute respiratory infections (ARI) is using antibiotics. This study aims to determine the sensitivity of several antibiotics to the bacteria that cause ARI. The design of this study is quasi-experimental. This sensitivity testing uses the disc diffusion method (Kirby Bauer). The antibiotics used are Ampicillin and Cefotaxime. The results obtained are that the antibiotic Ampicillin resistant by 86.26% and 13.63% are still sensitive to the bacteria that causes ARI. The same thing also happened to Cefotaxime antibiotics, most of which were resistant (59.09%), intermediate (9.09%), and most were still sensitive (31.81%) to bacteria that infect the respiratory tract. From the results obtained it can be concluded that the incidence of bacterial resistance to ampicillin and cefotaxime is very high against bacteria that cause ARI.